Therapist perceptions of experiential training for exposure therapy. Issue 3 (21st May 2023) - Frank, Hannah E.; Rifkin, Lara S.; Sheehan, Kate; Becker-Haimes, Emily M.; Crane, Margaret E.; Phillips, Katherine E.; Palitz Buinewicz, Sophie A.; Kemp, Joshua; Benito, Kristen; Kendall, Philip C.
Abstract: Background: Despite evidence for its efficacy, exposure therapy for anxiety is rarely used in routine care settings. Efforts to address one major barrier to its use – therapists' negative beliefs about exposure – have included therapist-level implementation strategies, such as training and consultation. Experiential training, in which therapists themselves undergo exposures, has recently demonstrated feasibility, acceptability and preliminary effectiveness for increasing exposure use. Aims: This study aimed to assess: (1) therapists' perceptions of experiential training and (2) barriers and facilitators to implementing exposure following training. Method: Therapists who underwent experiential training ( n= 12) completed qualitative interviews and quantitative questionnaires. Interviews were coded using an integrated approach, combining both inductive and deductive approaches. Mixed methods analyses examined how themes varied by practice setting (community mental health versus private practice) and exposure use. Results: Results highlight how therapist-level factors, such as clinician self-efficacy, interact with inner- and outer-setting factors. Participants reported positive perceptions of exposure after training; they noted that directly addressing myths about exposure and experiencing exposures themselves improved their attitudes toward exposure. Consistent with prior literature, issues such as insufficient supervisory support, organizational constraints, and client characteristics made it challenging to implement exposures. Discussion: Results highlight the benefits of experiential training, while also highlighting the need to consider contextual determinants. Differences in responses across practice settings highlight areas for intervention and the importance of tailoring implementation strategies. Barriers that were specific to therapists who did not use exposure (e.g. hesitancy about its appropriateness for most clients) point to directions for future implementation efforts.